An adsorption-precipitation model for the formation of injector external deposits in internal combustion engines. (15th October 2018) - Slavchov, Radomir I.; Mosbach, Sebastian; Kraft, Markus; Pearson, Richard; Filip, Sorin V.
Graphical abstract: Highlights: Kinetic model for gasoline injector deposit formation in engines is developed. Injector leakage causes accumulation of fuel near the nozzle post-injection. The leaked fuel degrades under the action of NOx and O2 in the quench layer. Radical chain oxidation takes place involving a branching reaction with NO. The pressure drop during the power stroke causes the leaked droplet to boil. Abstract: The occurrence of deposits on fuel injectors used in gasoline direct injection engines can lead to fuel preparation and combustion events which lie outside of the intended engine design envelope. The fundamental mechanism for deposit formation is not well understood. The present work describes the development of a computational model and its application to a direct injection gasoline engine in order to describe the formation of injector deposits and quantify their effect on injector operation. The formation of fuel-derived deposits at the injector tip and inside the nozzle channel is investigated. After the end of an injection event, a fuel drop may leak out of the nozzle and wet the injector tip. The model postulates that the combination of high temperature and the presence of NOx produced by the combustion leads to the initiation of a reaction between the leaked fuel and the oxygen dissolved in it. Subsequently, the oxidation products attach at the injector surface as a polar proto-deposit phase. The rate of deposit formation is predicted for two limiting mechanisms: adsorption and precipitation. The effects of the thermal conditions within the engine and of the fuel composition are investigated. Branched alkanes show worse deposit formation tendency than n-alkanes. The model was also used to predict the impact of injector nozzle deposit thickness on the rate of fuel delivery and on the temperature of the injector surface.